2012
DOI: 10.1007/s11356-012-1094-7
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of environmental contamination by alkylphenols

Abstract: Alkylphenols and alkylphenol ethoxylates (APE) are toxics classified as endocrine-disrupting compounds; they are used in detergents, paints, herbicides, pesticides, emulsifiers, wetting and dispersing agents, antistatic agents, demulsifiers, and solubilizers. Many studies have reported the occurrence of alkylphenols in different environmental matrices, though none of these studies have yet to establish a comprehensive overview of such compounds in the water cycle within an urban environment. This review summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(58 citation statements)
references
References 153 publications
3
54
0
1
Order By: Relevance
“…1A) are among the most important synthetic precursors for manufacturing a vast variety of chemical products including detergents, polymers, lubricants, antioxidants, emulsifiers, pesticides, and pharmaceuticals (1). Alkylphenols are also priority environmental pollutants because they are toxic, xenoestrogenic, or carcinogenic to wildlife and humans (2,3). The selective oxidation of the aliphatic C-H bonds in alkylphenols serves significant roles not only in generation of functionalized intermediates for synthesizing more downstream products (4), but also in biological degradation of these environmentally hazardous compounds (5).…”
mentioning
confidence: 99%
“…1A) are among the most important synthetic precursors for manufacturing a vast variety of chemical products including detergents, polymers, lubricants, antioxidants, emulsifiers, pesticides, and pharmaceuticals (1). Alkylphenols are also priority environmental pollutants because they are toxic, xenoestrogenic, or carcinogenic to wildlife and humans (2,3). The selective oxidation of the aliphatic C-H bonds in alkylphenols serves significant roles not only in generation of functionalized intermediates for synthesizing more downstream products (4), but also in biological degradation of these environmentally hazardous compounds (5).…”
mentioning
confidence: 99%
“…Alkylphenols (APs) and alkylphenol ethoxylates (APEs), high-performance non-ionic surfactants, are used in detergents, paints, herbicides, pesticides, emulsifiers, wetting and dispersing agents, antistatic agents, emulsifiers and solubilizers, and according to toxicological data sheet are classified as endocrine-disrupting compounds [184]. Their estrogenic activities are mainly dependent on their binding affinity for the ERs in vitro and in vivo [185,186].…”
Section: Alkylphenolsmentioning
confidence: 99%
“…Bergé et al (2012a) found that total concentrations of NPEO and their metabolites (mainly low-ethoxylated NPEOs and low-ethoxylated NPECs) were 0.10-1,179 μg L −1 (mean, 4.54 μg L ) in surface water. Some biodegradation intermediates, such as NP and low-ethoxylated NPEOs (NP 1-3 EO), exhibit estrogenic properties, and therefore, the biotransformation pathways of NPEOs have been widely studied using isolated bacteria (John and White 1998;Liu et al 2006Liu et al , 2013Lu et al 2008;Sato et al 2001Sato et al , 2003Ying et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Although the production of NPEOs has exhibited a decreasing trend in the USA, Canada, and the EU as a result of highly restrictive regulations (EU 2003;USEPA 2010), worldwide output increased from 300,000 t in 1994 to 500,000 t in 2002 (Berryman et al 2003;Ying et al 2002). The increase in consumption by emerging nations such as Brazil, Russia, India, and China has been considered as the main reason (Bergé et al 2012a).…”
Section: Introductionmentioning
confidence: 99%